Hubungan Konsumsi Fast Food dan Kualitas Tidur Terhadap Kejadian Obesitas di SMP Anak Indonesia Kota Makassar - Faisal, Nimrha; Muh. Khidri Alwi; Septiyanti (Window of Public Health Journal, 2025)
One of the habits of teenagers today is often consuming fast food. Teenagers now tend to consume fast food to create a modern self-image in society, and this habit will result in many teenagers becoming obese. This study aimed to analyze the relationship between fast food consumption and sleep quality and the incidence of overweight at SMP Anak Indonesia Baznas Makassar City. The study was conducted on May 20 - May 23, 2024. The population in this study was 40 students at SMP Anak Indonesia Baznas Makassar City. The method used was a quantitative method with a cross-sectional approach. The study showed a relationship between fast food consumption and obesity (p = 0.000). There is a relationship between sleep quality and overweight students at SMP Anak Indonesia Baznas (p = 0.000). Suggestions are expected so that schools can educate students about the importance of food consumed at and outside school and maintain students' sleep time, likewise for parents of students.